An Exploratory Study On The Monitoring And Evaluation Systems Of Non-Profit Organisations In The Western Cape - Thesen, Leila (Department of Social Development, 2024)
The implementation of Monitoring and Evaluation (herein referred to as M&E) activities and processes have become a critical tool for accountability, transparency and impact within NonProfit Organisations (herein referred to as NPOs) within South Africa. The study aimed to explore the implementation of M&E systems within NPOs in the Western Cape. The study utilised a qualitative exploratory research design as its purpose was to explore perceptions and experiences of NPOs within the Western Cape region. The sample size consisted of 16 NPOs. All participants were involved in M&E implementation within their organisations. Of the 16 NPOs represented, 5 were M&E personnel, 5 were CEOs/directors and 6 participants performed M&E duties as an added responsibility to their job titles. The study utilised a semi-structured interview guide for in-depth interviews that allowed for engagement between the researcher and participants. Furthermore, the study employed a thematic analysis for the qualitative data collected. The findings of the study showed that the perceptions of participants were influenced by various factors such as experience, training, and the M&E capacity of staff. Participants highlighted that M&E systems were implemented for programme implementation, accountability, and donor requirements. The experience of implementation was characterised by both positives and negatives which to varying degrees affected the implementation of the system. Challenges identified included system challenges; shortage of human and skilled resources as well as financial capacity to undertake M&E within organisations. Participants also highlighted M&E as a beneficial tool that allowed for programme support and implementation, accountability claims and funding opportunities. The findings from the research aims to contribute to the knowledge of M&E within NPOs. It is intended that the study's findings will contribute to the practice of M&E within NPOs as well as the research available on this field of study.